The Effectiveness and Impact of Arabic Language Learning Using Zoom Media During the Covid 19 Pandemic on Arabic Teachers at Madrasah Tsanawiyah Annajah Bekasi High School - Lalu Muhamad Syukur; Muhammad Arifin Hanif (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
The COVID 19 pandemic has had a significant impact in all fields, especially: economic, political, social and cultural. Including the field of education at all levels which also experienced very significant changes. At the tertiary level, for example, they must maintain the quality of graduates who are competent and qualified in their fields of expertise. Therefore, for a prospective teacher, MTS must have good skills and proficiency in teaching Arabic subjects, both online and offline. As this year we are facing a pandemic and require students to temporarily study at home on an online basis, and one of the ones being used is the ZOOM application. This article aims to describe how to train the competence of interior engineering teachers in teaching Arabic in the current epidemiological situation, in order to achieve the expected learning objectives. The method used in this study is descriptive qualitative, the data collected was generated from online observations and survey instruments. While the objectives are in the madrasah sanawiyah (MTS) teacher preparation program, at the Hidayatunnajah Islamic boarding school. The results of this study indicate that practice can encourage prospective teachers to understand Arabic material well, learn to prepare material and practice using learning applications, both online and offline, so they are not confusing and boring. The weakness that often occurs is not being familiar with educational material.